1980
DOI: 10.1210/endo-107-1-47
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin Neurons in the Rat Hypothalamus: An Immunocytochemical Study*

Abstract: Neurotensin was localized in the hypothalamic tissues of adult Sprague-Dawley rats by immunoperoxidase techniques. Visualization of perikarya was greatly enhanced by intraventricular administration of colchicine. Many perikarya containing neurotensin-like immunoreactivity were seen in the medial preoptic area, the periventricular hypothalamus, the parvocellular portion of the paraventricular nucleus, the arcuate nucleus, and the lateral hypothalamus in the perifornical area. There were moderate numbers of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(45 citation statements)
references
References 24 publications
3
42
0
Order By: Relevance
“…Labeling was conspicuously absent from the hypothalamic paraventricular nucleus and the adjacent periventricular region, areas previously reported to contain NTimmunoreactive cell bodies (8,18). One possible explanation for these results is that the content of NT/N mRNA in cells of these regions may be below the limits of detectability by in situ hybridization.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Labeling was conspicuously absent from the hypothalamic paraventricular nucleus and the adjacent periventricular region, areas previously reported to contain NTimmunoreactive cell bodies (8,18). One possible explanation for these results is that the content of NT/N mRNA in cells of these regions may be below the limits of detectability by in situ hybridization.…”
Section: Discussionmentioning
confidence: 80%
“…There was little, if any, signal associated with the paraventricular nucleus or the periventricular region, which was surprising because NT-immunoreactive cell bodies have been seen consistently in these areas (8,18). Labeled cells were observed in the arcuate nucleus, dorsomedial nucleus, and perifornical region, whereas the ventromedial nucleus was devoid of any labeling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both POMC/CART-and NPY/AgRP-containing neurons, in turn, project to other hypothalamic regions, including VMH, DMH, LHA, and the paraventricular nucleus (PVN) to regulate food intake and energy balance (Chiesi et al, 2001;Barsh and Schwartz, 2002;Berthoud, 2002;Funahashi et al, 2003). In the rat hypothalamus, NT neurons are widely distributed in the ARC, PVN, DMH, and LHA as immunocytochemistry studies have revealed (Kahn et al, 1980;Ibata et al, 1984). Leptin receptors (ObR b ) are also widely distributed in the ARC, PVN, and LHA (Mercer et al, 1996;Hakansson et al, 1998;Baskin et al, 1999a,b;Elmquist et al, 1999).…”
Section: Discussionmentioning
confidence: 99%